Personality remains: no effect of 3-week social status experience on personality in male fowl. (15th December 2017) - Favati, Anna; Udén, Eva; Leimar, Olof; Løvlie, Hanne
Abstract : Behavioral responses of male fowl did not depend on social rank after 3 weeks in stable groups, but were consistent over time for an individual. Theory suggests that stable social states, for example, stable social hierarchies, may lead to consistent variation in behavior, that is, variation in personality. Our results suggest that variation in personality is not a consequence of variation in social status and that personality is more important than current social position in determining individual behavior in stable groups. Abstract: Individuals often differ in behavior in a consistent way, that is, they show variation in personality. Understanding the processes explaining the emergence and maintenance of this variation is a current major topic in the field of animal behavioral research. Recent theoretical models predict that differences in various "states" can generate individual variation in behavior. Previous studies have mainly focused on endogenous states like metabolic rate or energy reserves, but theory also suggests that states based on social interactions could play important roles in shaping personality. We have earlier demonstrated short-term status-dependent variation in behavior in the domestic fowl ( Gallus gallus domesticus ), but whether such behavioral variation remains also after a longer period of time, is unknown. Therefore, we examine the influence of social status on variation in behavior, using experimental manipulation of social status in pairs of male domestic fowl. We scored males in 3 personality assays (novel arena test, novel object test, and aggression test) before and after 3 weeks in pairs as either dominant or subordinate. We observed individual consistency of behavior despite alteration of social status. We further found no support for social status acting as a state that generates variation in personality over the used time interval: social status had no significant effect on the change in behavioral responses between repeated personality tests. Our results suggest that personality is more important than current social situation for describing individual behavior in stable groups.